Gycaemic control and treatment profile amongst 20646 adult type 2 diabetes mellitus: a descriptive report - Chew, Boon How; Lee, Ping Yein; Ismail, Mastura; Cheong, Ai Theng; Taher, Sri Wahyu; Ahmad, Zaiton (Universiti Putra Malaysia Press, 2014)
An audit of Diabetes Control and Management-Diabetes Registry Malaysia (ADCM-DRM) was started to monitor the provision of diabetes care in the country. A total of 20,646 patients were registered in the registry until 31st December 2008. This report set out to determine the Type 2 diabetes controls and treatment profiles of these cohorts of patients. This was a registry-based observational study conducted from May to December, 2008. An online standard case record form was available for site data providers to register their diabetic patients aged 18 years old and above annually. Demographic data, diabetes duration, treatment modalities, as well as various risk factors and diabetes complications were reported. Data were analyzed using Data Analysis and Statistical Software (Stata) version 9. A total of 81 centres, 6 of which were hospitals, participated in this registry until 31st December 2008, contributing a total of 20646 patients. A majority of them (99.2%) had Type 2 diabetes mellitus. The mean HbA1c was 8.0% (SD 2.10), with 30.1% and 17.9% of the patients who attained HbA1c < 7% and HbA1c < 6.5%, respectively. Metformin was prescribed more than sulfonylurea while only 11% had insulin. A review of the diabetic care policy and strategies in the primary health care clinics is needed to implement a more effective treatment of diabetes in this country.